Confirmation of the "high-low" hypothesis: Living at altitude - training near sea level improves sea level performance - Levine, B. D.; Friedman, B.; Stray-Gundersen, J. (Medicine & Science in Sports & Exercise, 1996)
Competitive runners (M = 27; F = 12; 18-29 yr) were exposed to a series of control and manipulated conditions They were as follows: 1. Comprehensive sea-level lab testing for aerobic parameters, maximal steady state VO2 (ventilatory threshold), running economy, and velocity at VO2max, as well as a 5000 m time trial. 2. Supervised sea-level training for four weeks to establish control/baseline conditions. 3. Repeated testing as done in testing #1. 4. Four weeks of training camps. Ss were randomized to: (a) HL - live high (2500 m), train low (150 m) (N = 13); (b) HH - live high, train high (2500 m) (N = 13), and (c) LL - live low, train low (150 m) (N = 13). 5. Laboratory and performance tests were repeated once again. Results: 1. Both altitude groups significantly increased VO2max (HL 3.5, HH 4%) due to an increase in red cell mass volume (HL 6.3%, HH 11%). Controls did not change in either of these factors. 2. 5 km time improved in the three groups during initial sea-level training (22.3 sec). During the latter camps, it was further improved in HL group (13 sec), deteriorated in the HH group (3 sec) and the LL group (31 sec). 3. Velocity at VO2max improved only in the HL group (0.4 mph) as did maximal steady state VO2 (6.3%). It was concluded that 4 weeks of high-low training improves sea-level running performance more than an identical training camp at sea-level. The improvement is due to both a high altitude acclimatization effect (red cell mass, VO2max), and a low altitude training effect.